ПСИХОЛОГІЧНІ ОСОБЛИВОСТІ СПРИЙНЯТТЯ ЗОВНІШНЬОЇ РЕКЛАМИ (Педагогіка вищої та середньої школи, 2007)
In article is considered psychological aspect and character of models of perception of the consumer's external advertisement, her influence on humans.